The execution of Dual Language Programme (DLP) in Mathematics: Challenges faced by the primary school teachers in Samarahan district / Nor Hazizah Julaihi ... [et al.] - Julaihi, Nor Hazizah; Ahmad Bakri, Syah Runniza; Liew, Chin Ying; Salleh, Juliza (Universiti Teknologi MARA Cawangan Sarawak, 2024)
The Sarawak government is committed to enhancing students’ English competency, thereby improving their global competitiveness in the future workforce. This is reflected through the implementation of the Dual Language Program (DLP) in Sarawak, which mandates the schools to teach Science and Mathematics in English. While challenges in implementing the national DLP are often reported, studies specifically addressing the DLP Sarawak remain scarce. This study intends to add significant value to the existing knowledge about the challenges faced by the primary school teachers in executing the Mathematics DLP, particularly in Malaysia context. A survey research design was employed, using a questionnaire featuring both closed-ended and open-ended questions to collect data from 40 respondents. Descriptive and inferential statistics were used to analyse the data. It was found that 97.5% of the respondents used a blend of Bahasa Melayu and English during the Mathematics class with 55% of them using Bahasa Melayu more than English. Over one-third perceived “Fractions, Decimals, and Percentages" and "Time" as the most challenging topics. The Friedman test ranked challenges related to students’ English proficiency and their ability to learn Mathematics in English as the top two perceived challenges, followed by the lack of parental encouragement. Open-ended responses supported these findings and provided further explanations for the underlying reasons. The study highlights the need for concerted efforts from all stakeholders to address the significant challenges in teaching the Mathematics DLP. Limitations and recommendations for future studies are also discussed.